STUDI IMPEMENTASI STANDAR PELAYANAN MINIMAL (SPM) BIDANG KESEHATAN DASAR DI KOTA MAGELANG - Rengga, Aloysius (FORUM)
Abstract :Â The aims of these research is to explore the content and contex of SPM ( Minimal Standard of Public Services ) in Health Sector, how does local government implement these policy and how does society response on SPM implementation. The results of these research shows that in term of policy content actually consistence with local regulation whereas local government support in implementing SPM by regulating the Jamkesda. Total budget of Jamkesda is 1,3 billion rupiah which is allocated for poor family who aren't covered by Jamkesmas. In the context dimensions shows that there is no resistance against SPM policy. Most stakeholders says that SPM in Health Sector actually could improve health status and by increasing the health status could impact on improving family welfare. While in term of implementing these policy, its reflect that most indicators of SPM could be attain, but in term of immunization and family planning still lack and need to improve the performance. Societal response against SPM is quiet significance where most of family stated the health service is appropriate and most of people claimed that the policy should be improved in all aspect not just in basic health services.Keywords : Implementation, Minimal Standard of Services, Health Servicespermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3198